PERMAINAN KARTU SEBAGAI MEDIA PROMOSI NOVEL: JAKARTA THE GOLDEN RULE - Nindyaswari, Khansa Nabila; Akbar Pahala, Agam (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
The artist's concern about sales in previous novels became the background for the creation of a card game entitled "Jakarta: The Case”. This game is packaged with a role-playing mechanism, namely the player as the OSIS administrator who holds a meeting to find out which two people secretly violate the Golden Rule. The creation process in this work uses the research-led practice method, where the creation practice is based on research conducted by collecting data on the overall storyline of the novel "Jakarta".